Efektivitas Program Tabungan SUPRA (Simpanan Upacara Agama) di LPD Desa Adat Peguyangan - DESYANTARI, NI NYOMAN AYU; SUAMBA, I KETUT; DARMAWAN, DWI PUTRA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.1, Juli 2023, 2023)
Effectiveness of Savings Programs SUPRA (Religious Ceremony Savings) at the LPD Desa Adat Peguyangan Religious Ceremony Savings Program (SUPRA) is a savings program favored by LPD Desa Adat Peguyangan designed to accommodate the needs of the community who have long-term and planned needs. This research aims to analyze the effectiveness of religious ceremony savings program reviewed from the side of Lembaga Perkreditan Desa (LPD) and SUPRA savings customers. The sample of this study was 45 respondents, namely 2 LPD employees and 43 active savings customers SUPRA. The type of research used is descriptive qualitative and quantitative, data collection techniques are interviews, questionnaires and documentation. The results showed that most of the savings customers SUPRA productive age with a job as a private employee. On the LPD side, the number of customers has increased every year, but in 2020 it decreased due to many customers who are past due and the Covid-19 pandemic, which affects people's income, causing reduced saving activities, the amount of savings every year always increases and the percentage increase fluctuates, thus the SUPRA savings program is effective to run. From the perspective of SUPRA savings customers, based on indicators of program targeting accuracy, socialization, and programs viewed from customers who have not yet matured are determined to be very effective. For customers who have already matured, the use of the program is very effective, where customers use savings according to the original purpose. The enthusiasm of the public in participating in SUPRA savings is quite high, with customers who have already matured and return to participating in SUPRA savings. Public enthusiasm in participating in SUPRA savings is quite high, with customers who have matured and follow SUPRA savings.